Biocontrol potentiality of Burkholderia vietnamiensis nrv12 against the rice blast fungus magnaporthe oryzae - Loi, Nguyen Thi Thanh; Anh, Nguyen Tran Mai; Tuong, Ho Manh; Nguyen, Vu Thi Hanh; Tung, Quach Ngoc; An, Nguyen Thi Thu; Phat, Do Tien; Ha, Chu Hoang; Tien, Phi Quyet (Vietnam Journal of Biotechnology, 2024)
Rice blast disease, caused by the pathogenic fungus Magnaporthe oryzae, is a widespread infection leading to serious crop loss worldwide. In order to achieve sustainable agriculture, root-associated bacteria have been applied to manage fungal diseases and promote growth. The present study aimed to evaluate in vitro the growth-promoting ability and in vivo biocontrol activity against M. oryzae of rice rhizosphere bacterium. Out of sixty-eight isolates recovered from the rhizosphere of blast-infected rice plants, isolate NRV12 exhibited the highest antifungal activity against M. oryzae SH, with an inhibition percentage of 72.7±3.44%. By analysis of 16S rRNA sequence associated with morphology, physiological and biochemical tests, the strain was identified as Burkholderia vietnamiensis. In addition, NRV12 produced hydrolytic enzymes (amylase, cellulase, protease), indole acetic acid (IAA), exhibited nitrogen-fixing potential and the ability to solubilize phosphate and zinc. Innoculation with NRV12 significantly promoted in vivo rice seedling growth to 23.3% as compared to the non-bacteria-treated seedlings. Importantly, infected rice seedlings treated with NRV12 led to a 40% disease reduction in rice blast. These findings suggest that NRV12 is a valuable and promising isolate with biocontrol potential against rice blast caused by M. oryzae.